Automatic Task Receiving and Safety Device - Muhamad Ariandi; Jajang M Hambiah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Technological innovation always follows user needs and current trends that make it easier for users. One of the applications is in the form of an automatic task receiving and safety device. Automatic task receiving and safety device is an innovative solution that utilizes GM66 sensor, ESP32 module, ESP32 Cam, solenoid, limit switch and Automatic Transfer Switch (ATS). The system allows users to collect tasks or documents through an easily accessible Telegram Bot integration. This tool uses a GM66 sensor that functions to read Quick Response (QR) on the learning module, while the ESP32 functions as the central brain managing and transmitting data through a Wi-Fi network. This tool is also equipped with image capture capabilities using the ESP32 Cam Module. In the security section, this tool is equipped with a solenoid that functions as a mechanical lock on the door, while the switch functions to detect the state of the door on the tool and to ensure smooth operation by switching automatically between the main and backup electrical power sources this tool is equipped with an Automatic Transfer Switch (ATS). This innovation is to improve efficiency, security, and accessibility in the collection of tasks or documents. With IoT, users can easily manage their tasks in real-time with a 90% success rate.